2016
DOI: 10.1152/ajprenal.00545.2015
|View full text |Cite
|
Sign up to set email alerts
|

Role ofO-linkedN-acetylglucosamine modification in diabetic nephropathy

Abstract: Increased O-linked β-N-acetylglucosamine glycosylation (O-GlcNAcylation) is a known contributor to diabetes; however, its relevance in diabetic nephropathy (DN) is poorly elucidated. Here, we studied the process and enzymes of O-GlcNAcylation with a special emphasis on Akt-endothelial nitric oxide synthase (eNOS) and heat shock protein (HSP)72 signaling. Since tubular injury is the prominent site of DN, the effect of hyperglycemia was first measured in proximal tubular (HK2) cells cultured in high glucose. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…In line with our previous studies, we also observed severe structural and functional kidney damage in diabetic animals, which was improved by all RAASi (Banki et al 2012). According to the literature and our previous results, this renoprotection goes beyond decreasing blood pressure and can be related to other factors like lower oxidative stress (Fiordaliso et al 2006) or O-GlcNAc levels (Gellai et al 2016).…”
Section: Figure 6 Effect Of Profibrotic Factors and Renin-angiotensisupporting
confidence: 58%
See 2 more Smart Citations
“…In line with our previous studies, we also observed severe structural and functional kidney damage in diabetic animals, which was improved by all RAASi (Banki et al 2012). According to the literature and our previous results, this renoprotection goes beyond decreasing blood pressure and can be related to other factors like lower oxidative stress (Fiordaliso et al 2006) or O-GlcNAc levels (Gellai et al 2016).…”
Section: Figure 6 Effect Of Profibrotic Factors and Renin-angiotensisupporting
confidence: 58%
“…; Gellai et al . ). Some of these highlight the exceptional role of aldosterone antagonists (Taira et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Increased O-GlcNAcylation of cytoskeletal proteins is closely associated with the morphological changes in the podocyte foot processes in the glomerulus and in microvilli of proximal tubules in the diabetic kidney (252). Hyperglycemia-induced elevation of O-GlcNAcylation also contributes to the progression of diabetic nephropathy via inhibition of AKT/eNOS phosphorylation and HSP72 induction (253).…”
Section: Asbmb Award Article: Regulation Of Signaling and Transcriptionmentioning
confidence: 99%
“…Ohtsubo et al (10) reported that human pancreatic bcell-specific GnT-4a glycosyltransferase, which generates the core b1-4 GlcNAc linkage in N-glycans, has a protective effect against diabetes by increasing GLUT2 expression and maintaining insulin secretion. Differences of glycosylation, including O-GlcNAcylation, were reported to contribute to the progression of DKD in rats (11,12). There have been few reports about differences of glycosylation in patients with DKD because of technical obstacles to glycan analysis as a result of the complicated structures of these molecules and the time-consuming processes required for mass spectrometry (MS).…”
mentioning
confidence: 99%